The ocean sampling day consortium. - Kopf, A.; Bicak, M.; Kottmann, R.; Schnetzer, J.; Kostadinov, I.; Lehmann, K.; Fernandez-Guerra, A.; Jeanthon, C.; Rahav, E.; Ullrich, M.; Wichels, A.; Gerdts, G.; et al. (2015)
Ocean Sampling Day was initiated by the EU-funded Micro B3 (Marine Microbial Biodiversity, Bioinformatics, Biotechnology) project to obtain a snapshot of the marine microbial biodiversity and function of the world's oceans. It is a simultaneous global mega-sequencing campaign aiming to generate the largest standardized microbial data set in a single day. This will be achievable only through the coordinated efforts of an Ocean Sampling Day Consortium, supportive partnerships and networks between sites. This commentary outlines the establishment, function and aims of the Consortium and describes our vision for a sustainable study of marine microbial communities and their embedded functional traits.